Gating systems in the casting grinding balls technology - D. A. Volkov; A. D. Volkov; A. V. Efimenko (Литьë и металлургия, 2022)
The article presents a number of experimental and research works on the development of parameters of the casting technology of grinding balls by casting in a lined coquille (chill mould) with a vertical connector. The influence of a multi-level gating system on the efficiency of filling the mold cavity of lined coquilles with melt, on the quality of crystallization of large grinding balls, as well as on increasing the output of suitable casting was revealed. The influence of the thickness of the facing layer on the crystallization of large grinding balls is studied. The effect of modifiers containing barium, magnesium and cerium on the physical and mechanical characteristics of grinding balls and separately cast samples is investigated. Technology has been developed to eliminate contraction cavity in cast grinding balls by enhancing direct crystallization by partially replacing the facing layer with a heat-resistant water coating. The equipment for large-lot production of high-quality large grinding balls developed by OJSC “BELNIILIT” and competitive to world analogs is proposed.